Sex education in Sin(gapore) city: teaching sex from 1965 to 2000 - Ng, Queenie Yan Ying (Nanyang Technological University, 2022)
In The History of Sexuality (1976), Foucault argued that future and fortune of societies were tied not to the amount of uprightness of its citizens, their marriage rules and family organization, but to the manner in which each individual made use of his sex. As sexuality becomes increasingly wedded to the biopolitics of nation building, functioning both as a marker of its economic and biological wellness of nation-states, individual sexual contact and conduct rendered regulation. More importantly, during times of crisis, it warranted instruction. In early twentieth century America, pioneering sex education educators like Maurice Bigelow and Prince A. Morrow advocated for sex education to combat commercialized vice, venereal diseases, and the prevention of the ongoing population explosion. Decades later, during the 1980s, concerning global trends of soaring unplanned teenage pregnancy and abortion, alongside youth-on-youth violent sexual crimes sparked a renewed interest in sex education among developed nations, and garnered newfound support within the recently decolonized Southeast Asian region. Situating the discussion on Singapore, this thesis explores how sex education was introduced and conceived amidst the burgeoning crisis of sex, namely population explosion, teenage promiscuity, and AIDS epidemic. Analysing the cultural and scientific discourse on sex education from 1965 to 2000, this thesis argues that Singapore’s sex education, which responded to the state and professional anxieties over the matters of sexuality brought about by these social changes, ironically fostered even more problematic behaviours and views with regard to sex.